2009
DOI: 10.1080/14783360903037051
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of performance with soft factors and quality improvement

Abstract: The aim of this paper is to examine the influence of soft factors of quality management on firm performance, and analyse the link between quality improvement practice and firm performance. The study used data from 255 electrical and electronics (E&E) firms in Malaysia and it developed regression and correlation analysis to test these relationships. The findings showed that the following soft factors have significant influence on firm performance: management commitment, customer focus and employee involvement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…For the authors, such results confirm the impact of hard elements on the organization's performance is less significant than the impact of soft elements (Fotopoulos & Psomas, 2009). Abdullah et al (2009), analyzing dates from 255 Malaysia companies, found that some soft factors of quality management had significant influence on companies performance, as management commitment, customer focus and employee involvement. Also Prajogo (2005) demonstrated that the adoption of quality management principles for service and manufacturing companies significantly promoted a product quality improvement in terms of reliability, performance, duration and requirements conformity.…”
Section: Quality Managementsupporting
confidence: 49%
“…For the authors, such results confirm the impact of hard elements on the organization's performance is less significant than the impact of soft elements (Fotopoulos & Psomas, 2009). Abdullah et al (2009), analyzing dates from 255 Malaysia companies, found that some soft factors of quality management had significant influence on companies performance, as management commitment, customer focus and employee involvement. Also Prajogo (2005) demonstrated that the adoption of quality management principles for service and manufacturing companies significantly promoted a product quality improvement in terms of reliability, performance, duration and requirements conformity.…”
Section: Quality Managementsupporting
confidence: 49%
“…For TQM implementation, literature classified TQM practices in two groups: soft and hard TQM practices (Abdullah et al 2009;Green,2012;Fotopoulos and Psomas, 2009;Ho et al, 2001;Hoang et al, 2010;Ingelsson et al, 2012 ;Leavengood et al, 2012;Rahman and Bullock, 2005). Soft TQM practices are related to human aspects and associated with management concepts and principles (Dahlgaard-Park, 2012;Leavengood et al, 2012;Vouzas and Psychogios, 2007).…”
Section: Total Quality Managementmentioning
confidence: 99%
“…Based on the literature review (Abdullah et al 2009;Fotopoulos and Psomas, 2009;Ho et al, 2001;Hoang et al, 2010;Kaynak and Hartley, 2008;Leavengood et al, 2012;Powell, 1995;Rahman and Bullock, 2005;Saraph et al,1989;Vouzas and Psychogios, 2007), eight practices have been identified as critical for the successful TQM implementation in the Palestinian industrial SMEs: management leadership, customer focus, training, employee relations, quality data and reporting, supplier management, product and service design, and process management.…”
Section: Total Quality Managementmentioning
confidence: 99%
“…Irrespective of the absence of productivity measurement models which critically show the availability of ineffective inputs, there are enormous studies related to measuring the costs associated with ineffective inputs and investments made for preventing their existence (Abdullah, Uli, & Tarí, 2009;Freiesleben, 2005;Jurison, 1997;Schiffauerova & Thomson, 2006;Westlund & Lothgren, 2001). For example, Freiesleben (2005) developed an analytical model to show the expanding nature of ineffective inputs when products are progressing through subsequent stages.…”
Section: Introductionmentioning
confidence: 98%